The megaganacias and financial crisis of 2008 - Orozco Livia, Víctor (2014)
The voluminous profits from multinational conglomerates to the early 2000s, generated an excess of deposits that U.S. banks could not place, being in the dilemma of breaking the rules of the credit regulation. Lent, among others, who wished to acquire insolvent property and these caused a high rate of default. When financial assets created with guaranteed mortgage bonds “subprime”, which spread into the global banking crisis broke out in 2008, committing catastrophically banks and private companies, as happened in 1929 dimensions.